Find a training tool. ([s.l.] : SALTO-Youth Resource Centres)
Hundreds of useful tools for learning - for youth work and training activities! Created to help you find and share useful training Tools, the Toolbox for training is an online catalogue you can browse through freely or even contribute to!
Keywords: Jeugdwerk -- Internationaal; Jeugdwerk -- Methodiek; Materialen (spellen, methodieken, activiteiten).